Study on mechanism of increased allergenicity induced by Ara h 3 from roasted peanut using bone marrow-derived dendritic cells - MinJia Wang; Shuo Wang; Xiaodong Sun; ZhiRui Deng; Bing Niu; Qin Chen (Food Science and Human Wellness)
Little information was so far available about allergenic mechanism of the roasted peanut allergens during initial stages of allergy. The purpose of this study was to determine the influence of roasting (150 °C, 20 min) on biochemical and biological properties of Ara h 3, a major peanut allergen. Allergenicity of roasted peanut emulsion to mice, differences in uptakes between Ara h 3 purified from raw peanuts (named as Ara h 3-Raw) and that purified from roasted peanuts (named as Ara h 3-Roasted) by bone marrow-derived dendritic cells (BMDCs) and the implication of cell surface receptors involving in uptake, and changes in glycosylation and structure of Ara h 3 after roasting were analyzed in this study. This study suggested that roasting increased allergenicity of peanut to BALB/c mice. Maillard reaction and structural changes of Ara h 3 induced by roasting significantly altered the uptake of Ara h 3-Roasted by BMDCs, and modified Ara h 3 fate in processes involved in immunogenicity and hyper allergenicity, indicating that food processing pattern can change food allergenicity.